Advanced throwing on the potter's wheel Extended and altered forms - Hopper, Robin (PotteryVideos.com, 2004)
Robin Hopper demonstrates how a potter who possesses very ordinary size and strength can build tall pots by using a variety of extension throwing techniques including coil, slab, and thrown additions. He then shows how traditional shapes can be altered to produce innovative forms such as beaten, squared pots, squared spheres, and more abstract alterations of traditional forms. Throughout this video, he encourages you to use these approaches to develop your own unique creations.